Single and multicomponent adsorption of hexane isomers in the microporous ZIF-8 - Mendes, Patrícia A.P. (2015)
Single, binary and ternary breakthrough experiments of hexane (C6) isomers n-hexane (nHEX), 3-methylpentane(3MP), and 2,2-dimethylbutane (22DMB) were performed in the microporous zinc methyl-imidazolate metal–organic framework ZIF-8, covering the temperature range between 313 and 423 K and partial pressures up to 20 kPa. Adsorption equilibrium isotherms for nHEX were collected from single component breakthrough experiments who show that the sorption behavior of linear nHEX is totally different than the one observed for the branched isomers. Indeed, while nHEX is retained in the bed the branched paraffins spontaneously breakthrough leading to an efficient separation with a remarkable working capacity (25 wt%) for nHEX at 313 K and partial pressure 10 kPa. Langmuir isotherm is found to reasonably describe the adsorption equilibrium data of nHEX while the heat of sorption reaches 32.8 kJ/mol with Langmuir equilibrium affinity constants ranging from 1.73 to 0.0624 kPa 1 between 313 and 423 K, respectively. The ternary experiments (nHEX/3MP/22DMB) show a complete separation between nHEX and the branched isomers together with an adsorbed amount of nHEX similar to the one found in single component experiments. In the binary experiments (3MP/22DMB) the separation and sorption capacity is negligible. A fixed bed adsorption dynamic model is used to demonstrate that the complete separation of nHEX from the branched paraffins is due to a spontaneous breakthrough ofthe branched paraffins due to its lower diffusivity values when compared with nHEX.